Coexistence of papulonecrotic tuberculide with lichen scrofulosorum - Das Jayanta; Sengupta Sujata; Mitra Subhabrata; Gangopadhyay Asok (Wolters Kluwer Medknow Publications, 2010)
Tuberculides, the supposedly immunologic reactions to the products of dead Mycobacterium tuberculosis bacilli deposited in the skin from distant foci of tubercular infection, are presently considered to be of two types-papulonecrotic tuberculide and lichen scrofulosorum. Simultaneous occurrence of both the types in the same patient is very rare. We report the case of an adult male without any known internal tubercular focus who showed two types of skin lesions, clinically typical and histopathologically consistent with the diagnoses of papulonecrotic tuberculide and lichen scrofulosorum, occurring simultaneously. Polymerase chain reaction showed the presence of Mycobacterium tuberculosis DNA in papulonecrotic tuberculide type of lesion, and both types of lesions responded promptly to anti-tubercular drugs.